2014
DOI: 10.5005/jp-journals-10071-23383
|View full text |Cite
|
Sign up to set email alerts
|

Renal Replacement Therapy in Acute Kidney Injury: Which Mode and When?

Abstract: Renal replacement therapy (RRT) for acute kidney injury (AKI) patients in an intensive care unit (ICU) presents unique problems of providing biochemical and fluid removal in patients with unstable circulations, inotropes, and increased capillary permeability. Although no individual modality has been shown to confer a mortality benefit, it is assumed that continuous therapies like peritoneal dialysis (PD) and venovenous hemofiltration or hemodiafiltration may be better tolerated by the patient with hemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Continuous renal replacement therapy is often utilized in renal replacement therapy for critically ill patients, especially for those with hemodynamic instability ( 21 ). CRRT treatment for critically ill patients removes excess water and certain potentially toxic macromolecular compounds ( 22 ). Several studies had shown that insufficient CRRT treatment would result in adverse outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous renal replacement therapy is often utilized in renal replacement therapy for critically ill patients, especially for those with hemodynamic instability ( 21 ). CRRT treatment for critically ill patients removes excess water and certain potentially toxic macromolecular compounds ( 22 ). Several studies had shown that insufficient CRRT treatment would result in adverse outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further, procedural details such as the type of catheter (rigid vs. flexible) or buffer (lactate acetate vs. bicarbonate) used [ 3 ] and the time of initiation of KRT may be potential confounders but were not reported by most of the included studies. Finally, this systematic review and meta-analysis was conducted to include different techniques of the three primary dialysis modalities, and, therefore, we did not search for studies reporting mortality outcomes with CRRT, HD, or PD techniques alone.…”
Section: Discussionmentioning
confidence: 99%
“…A severe decline in kidney function (GFR < 15 ml/min/1.73 m 2 ) due to either AKI [ 3 ] or CKD [ 4 ] necessitated life-saving support using kidney replacement therapy (KRT). The global use of KRT has increased by 43% from 1990 to 2017 [ 1 ], mirroring the global increase in the incidence of AKI [ 5 ] and CKD [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected for the following parameters: age, sex, total fluid input and output, serum creatinine, urea, procalcitonin, CRP, Hb, blood lactate, arterial and venous blood gas analysis, parameters of coagulation system and liver, serum electrolytes, and arginine, ornithine, ADMA, SDMA, DMA, and citrulline. Additionally, patients were assessed with respect to their need for CRRT [ 31 ].…”
Section: Methodsmentioning
confidence: 99%